O18. An interactive tool to improve patient throughput in radiotherapy. (September 2016) - Botha, J.; Burger, H.; Trauernicht, C.
Abstract : Introduction: In 2015 the Departments of Medical Physics and Radiation Oncology tried to find a way to increase the patient numbers on the treatment units. Game boards were designed to allow each treatment unit to come up with an innovative way of structuring and organizing their daily tasks on the machines. The game boards can immediately give an indication of the possible output for that particular arrangement of tasks. Game boards were manufactured, but had the disadvantage of not being able to save the data for later use. The game boards were limited to a twelve hour clock face and only had a direct input-output relationship. Materials and methods: Various software packages were considered before choosing Unity3D, which is a cross-platform 3D engine and allows for programming using C#. The 3D models were created using Blender. The objective was to make the tool as flexible as possible, so that the tool could be scaled to other departments as well. The game represents a clock face with user-defined time intervals. Game tokens represent the tasks, resources and outputs. They are added to the time slots when the game is played. Output rules specify what output will result from which combination of tasks. The aim is to optimize this output. Results: A 3-dimensional electronic game was created, which mimics the physical board game, but also provides improvements in automating the calculation of the outputs, and having the ability to save the game. In addition, the electronic version of the game has the potential for more complex interaction modelling of the factors affecting the outcome. Conclusion: The game board can be an effective management tool for allowing staff input to improve patient throughput. Converting the game board to an electronic version improves the playability, flexibility and usability of the tool.